Analysis of the Readiness for Implementing Deep Learning Curriculum in Madrasah from the Perspective of Educators - Fil Isnaeni; Septian Arief Budiman; Nurjaya Nurjaya; Mukhlisin Mukhlisin (Institut Agama Islam Daruttaqwa Gresik, 2025)
This study explores the readiness of madrasahs to implement a deep learning-based curriculum from the perspective of educators. As technology advances and digital skills become increasingly important in education, integrating deep learning approaches is expected to improve learning quality in Islamic schools. Using a qualitative case study method, this research was conducted in several madrasahs that have begun incorporating technology into their teaching practices. Data were collected through in-depth interviews with educators and classroom observations. The findings show a strong interest among teachers in applying deep learning strategies. However, several challenges hinder effective implementation, including limited access to technology, lack of professional training, and insufficient understanding of deep learning concepts. Despite these issues, most teachers expressed willingness to adapt and learn, provided they received adequate support from schools and the government. The study concludes that three key factors determine the success of deep learning curriculum implementation in madrasahs: (1) continuous professional development for teachers, (2) sufficient technological infrastructure, and (3) a deeper understanding of the pedagogical value of deep learning. This study implies that successful implementation requires collaboration from all parties. The government should provide policies and funding for teacher training and technology access. Madrasahs must facilitate ongoing learning opportunities, while teachers should remain open to improving their digital and pedagogical skills. With strong collaboration, deep learning can be effectively integrated, enhancing the quality of Islamic education in the digital age.